Midwestern restaurant association member attitudes about hiring individuals with a criminal background and a food handler certificate or food protection manager certification - Holliday, Mitchel K. (University of Wisconsin--Stout, 2018)
Correctional food service training programs have attempted to utilize certificates and certifications to impact recidivism; however, no literature was found on if individuals responsible for hiring employees would be more likely to hire individuals with a criminal background who have obtained these certificates or certifications. The purpose of this study was to identify if a food handler certificate or food protection manager certification would increase the likelihood individuals with criminal backgrounds would be hired into different types of jobs in the food service sector. A total of 1798 Minnesota and Wisconsin Restaurant Association Members were invited to participate via their respective listservs. Sixty-nine members responded. The results of the study indicated desired training for individuals with criminal backgrounds varied across positions with a preference for correctional training, with and without the offering of a food handler certificate or food protection manager certification, to be offered in coordination with a college/university culinary arts program. Individuals with a criminal background and a food handler certificate and food protection certification manager certification had a higher mean likelihood of being employed than those without across all positions. Work experience was the most desired type of training for individuals with a criminal background. Lastly, work experience and offense history were identified as the main reasons reported for hiring individuals with a criminal background.
Keywords: Prisoners; Restaurateurs; Food service employees; Recidivism